Comparison of Various Vagal Maneuvers for Supraventricular Tachycardia by Network Meta-Analysis - Huang, Edward Pei-Chuan; Chen, Chi-Hsin; Fan, Cheng-Yi; Sung, Chih-Wei; Lai, Pei Chun; Huang, Yen Ta (Frontiers in Medicine, 2022)
Background Vagal maneuvers (VagMs) are recommended as the first-line treatment of supraventricular tachycardia (SVT). However, the optimal type of VagMs remains unproven. Aim This study aims to compare the effectiveness and adverse events amongst VagMs on SVT via network meta-analyses (NMAs). Methods We systematically searched randomized controlled trials (RCTs) that involved adults with SVT and compared VagMs without language restrictions. We determined the initial and final responses of conversion rate to sinus rhythm and adverse events. Risk of bias (RoB) was appraised by Cochrane revised tool, and contribution matrix was calculated. NMAs were synthesized using frequentist random-effects model and presented as relative risk (RR) with 95% CI. The order of probability was presented as surface under the cumulative ranking curve analysis (SUCRA). Sensitivity analysis was performed using both Bayesian and frequentist approach with fixed- or random-effects models. Certainty of evidence (CoE) was rated by using the Grading of Recommendations, Assessment, Development, and Evaluations methodology. Results Fourteen RCTs with 2,180 patients were enrolled. Small portion of mixed estimates was contributed from high overall RoB studies. Compared with carotid sinus massage (CSM), the modified Valsalva maneuver (MVM) was the most effective VagM after initial performance [SUCRA: 0.9992, RR: 5.47 (1.77–16.93)] and at the end of study [SUCRA: 1.0000, RR: 3.62 (2.04–6.39), CoE: high]. The standard VM did not elicit better conversion rate to the sinus rhythm than CSM at the initial response [SUCRA: 0.4395, RR: 1.97 (0.63–6.15)] and at the end of the study [SUCRA: 0.4795, RR: 1.64 (0.94–2.87), CoE: moderate]. The SUCRA value of CSM at the initial and final responses was the least one amongst three VagMs (0.0613 and 0.0205, respectively). Adverse events amongst three VagMs were similar (CoE: low). Sensitivity analyses yielded consistent results. Conclusion We recommended MVM as the first choice of VagM for rhythm conversion before the pharmacological management of SVT.